CoP/C hollow hybrids inducing abundant active interfaces and fast electron transfers to activate peroxymonosulfates for bisphenol A degradation. (June 2021) - Zhou, X.; Tang, Y.; Xu, X.; Zhou, X.; Zhao, G.; Zhou, M.; Wan, G.; Wang, G.
Abstract: Traditional methods limit the amount of interface active sites and electron transfer efficiency in supported catalysts, which makes the practical catalysis performance of heterogeneous catalysts for advanced oxidation processes not really perfect. In this article, novel CoP/C hollow hybrids with abundant active interfaces and high surface electron transfer were successfully synthesized. The carbon matrix and CoP combined uniformly and formed a stable conductive network throughout structure. The unique structure of CoP/C endowed them with high catalysis efficiency, as well as low environmental harm in actual bisphenol A (BPA) degradation. BPA removal rate could reach to 100% within 10 min, and the leaching of cobalt ions was far lower than the wastewater discharge standard. The efficiency of BPA degradation was positively correlated with the dosages of CoP/C and peroxymonosulfate (PMS). The CoP/C/PMS/BPA system also showed the impressive degradation performance at a wide pH range (pH = 3–11) and even in practical applications, exhibiting outstanding stability and reusability. Furthermore, through radical quenching experiments, electron paramagnetic resonance test and electrochemical analysis, an exhaustive research was conducted to elucidate the PMS activation mechanism by CoP/C. Graphical abstract: Image 1 Highlights: ● Novel s CoP/C hollow hybrids were successfully synthesized. ● CoP/C nanohybrids with a stable conductive network facilitate the electron transfer. ● CoP/C hybrids exhibited excellent catalytic activities for the oxidative degradation of BPA. ● The electron transfer mechanism was clarified by electrochemical test, EPR, and XPS analysis. ● CoP/C showed a considerable potential in actual wastewater treatment.